The city as a tangled bank : urban design versus urban evolution - Farrell, Terry (West Sussex : Wiley, 2014)
Here Sir Terry Farrell, who has built an international career as an architect-planner, encourages other planners and architects to follow the biologists-look at, learn from, and, indeed, admire the nature of the forces that drive the change, and then with humility and respect work with them to nudge, anticipate and prepare for where it takes us. Searching for patterns within the apparent turbulence and complexity, he analyses the notions of urban design and urban evolution and examines whether or not they need necessarily be seen as opposing one another. The first two chapters discuss emerg.
Includes bibliographical references (pages 186-187) and index.
Print version record.
Keywords: City planning -- Philosophy; City planning; Emergence (Philosophy); Farrell, Terry; Pedestrian areas; POLITICAL SCIENCE -- Public Policy -- Regional Planning; City planning -- Philosophy; Electronic books